ANALISIS READINESS FOR CHANGE TERHADAP KINERJA: PERSPEKTIF KARYAWAN KONTRAK DI MASA PANDEMI COVID-19 - Asbari, Masduki; Novitasari, Dewiana; Silitonga, Nelson; Sutardi, Didi; Gazali (Fakultas Ekonomi Universitas IBA, 2020)
This study aimed to measure the effect of transformational leadership on employee performance of the employee of a HVAC industry in Tangerang which are mediated by readiness for change. Data collection was done by simple random sampling technique and the returned and valid questionnaire results were 224 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership have not significant effect on the employee performance, but transformational leadership have a positive and significant effect on readiness for change. This study conclude also that readiness for change have a positive and significant effect on relationship between transformational leadership and employee performance. Readiness for change as fully mediator. This new research proposed a model for building employee performance among the employee of a HVAC industry in Tangerang through enhancing transformational leadership practice with readiness for change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.